Perceived Usefulness as Key Stimulus to the Behavioral Intention to Use 3G Technology - Budi, Andy Susilo Lukito; Efendi, Efendi; Dahesihsari, Rayini (ASEAN Marketing Journal, 2021)
A new technology usually faces the challenge to be accepted by consumers. Because of the unique features of new technology, it needs certain approaches to enhance its acceptance. Technology Acceptance Model (TAM) is widely used to study the behavior of organizations and consumers in ac-cepting a new technology. A modified TAM model is applied in the current study to test the impact of advertising appeals of perceived usefulness, perceived ease of use, and social factors on behavioral intention to use 3G technology. Experimental method is utilized on four groups (30 people each) of undergraduate students of Atma Jaya Catholic Univesity. The result shows significant impact of the advertising multimedia exposed to the subjects, specifically perceived usefulness. It is concluded that perceived usefulness is the most salient reason among Atma Jaya Catholic University’s students in consuming 3G technology.